Method for manufacturing electrode and method for manufacturing battery

By controlling the humidity and pressing method of the active material layer during the electrode manufacturing process, the problems of electrode deformation and damage are solved, and the production efficiency and performance of the electrode and battery are improved.

JP2025018739AActive Publication Date: 2025-02-06KK TOSHIBA

Patent Information

Application Number
JP2023122716
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-02-06
Estimated Expiration
2043-07-27

AI Technical Summary

Technical Problem

Existing electrodes are prone to deformation and damage during the manufacturing process, which is difficult to deal with, resulting in defects during the manufacturing process.

Method used

By coating the slurry containing titanium niobium oxide and water on the current collector, the humidity of the active material layer is controlled below 600 ppm and the humidity is controlled using the Karl Fischer method during pressing and lamination to ensure that the electrode does not deform during transportation.

Benefits of technology

Effectively prevent deformation and damage of electrodes during transportation, reduce manufacturing defects, and improve production efficiency and battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018739000001_ABST
    Figure 2025018739000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing an electrode and a method for manufacturing a battery which can reduce generations of failures in the manufacturing.SOLUTION: According to an embodiment, there is provided a method for manufacturing an electrode including the steps of: applying a slurry including at least one of a niobium-containing oxide and a titanium-containing oxide and water to a collector and obtaining a structure; drying the slurry and forming an active material containing layer; pressing the structure; laminating plural structures to obtain the laminate body, drying the laminate body while pressing both outermost layers of the laminate body, thereby setting the water content amount of the active material containing layer to determine by the Karl-Fischer method to be 600 mass ppm at a maximum.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The embodiments relate to a method for manufacturing an electrode and a method for manufacturing a battery. [Background technology]

[0002] In order to improve the life performance of electrodes using niobium titanium oxide, a hydrophilic binder such as carboxymethyl cellulose (CMC) has been added to the electrodes. However, this electrode has a problem in that it is easily bent when made large, making it difficult to handle during manufacturing. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-53944 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the embodiments is to provide a method for manufacturing an electrode and a method for manufacturing a battery that can reduce the occurrence of defects during manufacturing. [Means for solving the problem]

[0005] According to an embodiment, the present invention includes a step of obtaining a structure by applying a slurry containing at least one of a niobium-containing oxide and a titanium-containing oxide and water to a current collector; drying the slurry to form an active material-containing layer; pressing the structure; and laminating a plurality of such structures and drying both outermost layers of the resulting laminate under pressure, thereby reducing the moisture content of the active material-containing layer to 600 ppm by mass or less as determined by the Karl Fischer method.

[0006] According to the embodiment, a method for producing an electrode group includes the steps of: using the electrode obtained by the method according to the embodiment as a first electrode; and disposing a separator between the first electrode and a second electrode to produce an electrode group; A step of housing the electrode group in an exterior member; and causing the electrode group housed in the exterior member to retain a non-aqueous electrolyte. [Brief description of the drawings]

[0007] [Figure 1] FIG. 4 is a flow diagram illustrating an example of a method according to an embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing an example of coating and drying in the method of the embodiment. [Diagram 3] FIG. [Figure 4] 4 is a cross-sectional view taken along line IV-IV of the structure shown in FIG. 3. [Diagram 5] 4 is a cross-sectional view taken along line VV of the structure shown in FIG. 3. [Figure 6] FIG. 4 is a side view showing a state in which a portion of the structure without an active material-containing layer is sandwiched between a pair of rollers. [Figure 7] FIG. 2 is a cross-sectional view of a structure in which a portion without an active material layer is sandwiched between a pair of rollers, the cross-sectional view being cut in a direction perpendicular to the conveying direction. [Figure 8] FIG. 2 is a schematic perspective view showing an example of a roll of a structure. [Figure 9] FIG. 4 is a schematic diagram showing an example of pressing and winding in the method of the embodiment. [Figure 10] FIG. 10 is an enlarged cross-sectional view showing the pressing process shown in FIG. [Figure 11] FIG. 4 is a schematic plan view showing an example of cutting in the method of the embodiment. [Figure 12] FIG. 2 is a plan view showing an electrode manufactured by the method of the embodiment. [Figure 13] FIG. 13 is a plan view showing an electrode having a wrinkled tab. [Figure 14] FIG. 4 is a plan view showing a housing used in the second drying step of the method according to the embodiment. [Figure 15] 15 is a cross-sectional view of the housing shown in FIG. 14 taken along line XV-XV. [Figure 16] FIG. 2 is a partially cutaway perspective view of a battery manufactured by the method of the embodiment. [Figure 17] FIG. 17 is an enlarged cross-sectional view of a portion indicated by B in FIG. 16. [Figure 18] FIG. 4 is a perspective view showing another example of a laminated electrode group manufactured by the method of the embodiment. [Figure 19] 4 is a cross-sectional view of a battery manufactured by a method according to an embodiment, taken in a direction perpendicular to the terminal extending direction. FIG. [Figure 20] FIG. 20 is an enlarged cross-sectional view of a portion indicated by A in FIG. 19 . DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] (First embodiment) The first embodiment relates to a method for manufacturing an electrode.

[0009] An electrode produced by coating a current collector with a slurry containing at least one of a niobium-containing oxide and a titanium-containing oxide and water, drying, pressing, and cutting the current collector, is prone to bending when the electrode area is increased, which can result in defects such as the electrode bending and deforming when transported by a transport device such as a vacuum, or the electrode falling off the transport device.

[0010] The method of the embodiment includes a step of obtaining a structure by applying a slurry containing at least one of a niobium-containing oxide and a titanium-containing oxide and water to a current collector; drying the slurry to form an active material-containing layer; pressing the structure; and laminating a plurality of such structures and drying both outermost layers of the resulting laminate under pressure, thereby reducing the moisture content of the active material-containing layer to 600 ppm by mass or less as measured by the Karl Fischer method.

[0011] According to the method of the embodiment, in the manufacture of an electrode or a battery, when the electrode is transported to the next process or a predetermined position, the electrode has a suitable hardness and is therefore unlikely to bend even if the electrode area is large. As a result, it is possible to prevent the electrode from bending and falling from the transport device during transport, thereby preventing defects such as damage to the electrode (chipping, cracking, peeling, etc.) due to falling and failure of the electrode to be transported to the predetermined position. In addition, it becomes easy to automate the process of manufacturing a stacked electrode group by disposing a separator between this electrode and the counter electrode.

[0012] The method of the embodiment will be described below with reference to FIGS.

[0013] The method for producing an electrode according to the embodiment may include steps S1 to S5 shown in FIG.

[0014] First, the slurry coating S1 and the first drying S2 will be described.

[0015] 2 shows an example of an apparatus used in the slurry coating S1 and the first drying S2. This apparatus includes a slurry coating apparatus 20, a drying furnace 21, and a curvature correction section 22. The slurry coating apparatus 20 includes a slurry storage section 23, a first die coater 24, and a second die coater 25. A current collector roll 26 on which a current collector 3a (e.g., a negative electrode current collector 3a) to be treated is wound in a roll shape is disposed on the upstream side of the transport path F1. A winding roller 27 is disposed on the downstream side of the transport path F1. The current collector 3a sent out from the current collector roll 26 moves along the transport path F1 and is wound up by the winding roller 27.

[0016] The first die coater 24 is located above the current collector 3a moving along the transport path F1. The second die coater 25 is located below the current collector 3a moving along the transport path F1. The second die coater 25 is located downstream of the first die coater 24. The slurry storage unit 23 supplies the slurry to the first die coater 24 via a slurry supply flow path 23a. The slurry storage unit 23 also supplies the slurry to the second die coater 25 via another slurry supply flow path (not shown). The slurry storage unit 23 includes, for example, a slurry storage container and a liquid feed pump (not shown).

[0017] The drying furnace 21 is disposed downstream of the conveying path F1 from the slurry coater 20. The drying furnace 21 has an inlet (not shown) through which the current collector 3a (hereinafter referred to as the structure) coated with the slurry is inserted into the drying furnace 21, and an outlet (not shown) through which the structure that has moved within the drying furnace 21 along the conveying path F1 is discharged.

[0018] The curvature correction unit 22 is disposed downstream of the first die coater 24 and the second die coater 25, at any one or more locations in the drying furnace 21, and between the drying furnace 21 and the take-up roller 27. By disposing the curvature correction unit 22 downstream of the first die coater 24 and the second die coater 25, the surface coated by the first die coater 24 and the second die coater 25 is less affected by the curvature correction unit 22, and the flatness of the coated surface can be maintained. As shown in Figs. 6 and 7, the curvature correction unit 22 can be composed of a pair of rollers. The curvature correction unit 22 is composed of a guide roller 28 located above the structure moving along the conveying path F1, and a conveying roller 29 located below the structure moving along the conveying path F1. The guide roller 28 and the conveying roller 29 are each formed of a metal such as iron or stainless steel.

[0019] Next, the slurry coating step S1 and the first drying step S2 will be described in detail.

[0020] First, a slurry containing at least one of a niobium-containing oxide and a titanium-containing oxide and water is supplied to the slurry storage section 23. The slurry is prepared, for example, by dispersing at least one of a niobium-containing oxide and a titanium-containing oxide, a conductive agent, and a binder in a solvent containing water. The active material, the conductive agent, the binder, and the solvent will be described later. The slurry supplied to the slurry storage section 23 is supplied to the first die coater 24 and the second die coater 25 by a slurry supply passage. The current collector 3a sent out from the current collector roll 26 moves along the transport path F1, and in the first die coater 24, the slurry is coated (applied) on one side of the current collector 3a, except for both ends perpendicular to the transport direction (longitudinal direction). The current collector (structure) with the slurry applied on one side moves along the transport path F1, is introduced into the drying furnace 21 from its entrance, and is subjected to a first drying S2 in the drying furnace 21, after which it is discharged from the exit of the drying furnace 21 and taken up by the take-up roller 27. As a result, the structure is wound into a roll.

[0021] Next, the other uncoated surface of the current collector 3a is sent from the rolled structure to the second die coater 25. The other uncoated surface of the current collector 3a is coated (applied) with slurry, except for both ends perpendicular to the conveying direction (longitudinal direction). This completes the slurry application S1. The current collector (structure) with the slurry coated on the other side moves along the conveying path F1, is introduced into the drying furnace 21 from the entrance of the drying furnace 21, is subjected to the first drying S2 in the drying furnace 21, and is then discharged from the exit of the drying furnace 21 and taken up by the take-up roller 27. This completes the first drying S2.

[0022] In the structure 10 shown in Figs. 3 to 5, the region where the slurry is applied to form an active material-containing layer is indicated as 3b, and the region where the slurry is not applied and no active material-containing layer exists is indicated as 3a. The region 3b of the structure where the slurry is applied shrinks in the short side direction due to drying in the drying furnace 21. On the other hand, both end portions 3a perpendicular to the transport direction (longitudinal direction) of the structure are not applied with the slurry, and therefore hardly shrink due to drying. Due to the stress difference caused by this phenomenon, the end portions where the active material-containing layer is not formed tend to bend. The direction of the force that tries to bend is indicated by the reference symbol 30 in Fig. 2.

[0023] After the slurry is applied, the active material-containing layer-free portions located at both ends of the short side direction of the structure are moved to the take-up roller 27 along the transport path F1 while being sandwiched between the guide roller 28 and the transport roller 29, as shown in Figs. 6 and 7. As a result, the structure can be moved along the transport path F1 while being stretched in a direction (short side direction) perpendicular to the transport direction (longitudinal direction), so that curvature due to drying of the slurry can be suppressed. Note that Fig. 7 shows an example in which the active material-containing layer 3b is formed on both sides of the current collector 3a, but after the curvature correction is performed by the guide roller 28 and the transport roller 29 at the stage of forming the active material-containing layer 3b on one side of the current collector 3a, the curvature correction may be performed by the guide roller 28 and the transport roller 29 when the active material-containing layer 3b is formed on the other side of the current collector 3a. Fig. 8 shows an example of a roll 31 of the structure wound by the winding roller 27. In Fig. 8, the winding core located at the winding center of the roll 31 of the structure is omitted.

[0024] Here, the first drying may be performed so long as the moisture content of the active material-containing layer measured by the Karl Fischer method is greater than the moisture content of the active material-containing layer measured by the Karl Fischer method after the second drying S5. The first drying may be performed, for example, so that the active material-containing layer has a moisture content of 1000 mass ppm or more and 10000 mass ppm or less measured by the Karl Fischer method. This can prevent the structure from being broken or chipped during pressing and cutting, at least when pressing and cutting are performed. A method for measuring the moisture content by the Karl Fischer method will be described. Samples (including the current collector) measuring 3 mm x 2 cm are cut out from the short side at the beginning of winding and the short side at the end of winding of the roll 31 of the structure. The two prepared samples are prevented from drying before the moisture content is measured. Specifically, for example, after preparing the samples, they are placed in a sealed container and taken to a measuring device. Alternatively, the samples are prepared at a location where the measuring device is located, and the measurement is performed immediately on the spot.

[0025] The moisture content of each of the two samples prepared as described above is measured by coulometric titration using a Karl Fischer moisture meter (VA-06, manufactured by Mitsubishi Chemical Analytech Co., Ltd.). Specifically, the sample is heated to 140°C and nitrogen gas is introduced at a flow rate of 200 ml / min. The moisture content is calculated from the amount of electricity consumed in the reaction between water and iodine. The average of the two moisture contents obtained is regarded as the moisture content of the slurry by the Karl Fischer method.

[0026] The short side of the structure at the start of winding may be, for example, the short side where the structure emerges from the outlet after passing through a drying oven, whereas the short side of the structure at the end of winding may be, for example, the position where the head is released after coating is completed.

[0027] By making the moisture content of the active material-containing layer 1000 mass ppm or more by the Karl Fischer method, it is possible to suppress the occurrence of breakage and chipping in the structure during pressing performed after drying. By making the moisture content 10000 mass ppm or less, it is possible to prevent defects during pressing, such as the slurry adhering to the press roller during pressing. The more preferable range of the moisture content is 1500 mass ppm or more and 5000 mass ppm or less.

[0028] The drying temperature of the slurry can be in the range of 25°C or more and 100°C or less, and more preferably 25°C or more and less than 80°C. By setting the drying temperature in the range of 25°C or more and 100°C or less, it is possible to remove the moisture in the material constituting the active material-containing layer while leaving a predetermined amount of moisture. When the temperature is 25°C or more and less than 80°C, the drying time can be, for example, in the range of 10 seconds or more and 600 seconds or less. More preferably, it is 60 seconds or more and 240 seconds or less. Here, the drying temperature is, for example, the temperature inside the drying furnace 21.

[0029] The water content of the active material-containing layer as determined by the Karl Fischer method can be adjusted, for example, by the drying temperature, drying time, composition of the active material-containing layer, and the like.

[0030] The structure 10 that has been subjected to the first drying S2 is wound up by a winding roller 27. Moisture-containing structures may come into contact with each other and transfer unevenness to each other. By adjusting the winding tension according to the moisture content of the active material-containing layer of the structure 10, it is possible to avoid the phenomenon of transfer, in which the active material-containing layer is compressed and unevenness occurs on the surface. The winding tension can be set, for example, in the range of 5 N to 30 N.

[0031] The coating S1 and the first drying S2 may be performed on one side of the current collector or on both sides of the current collector at the same time. For example, the slurry is applied to one side of the current collector, and then the drying conditions of the slurry are adjusted to form an active material-containing layer containing moisture of 1000 ppm by mass to 10000 ppm by mass as measured by the Karl Fischer method. The slurry is then applied to the other side of the current collector, and the slurry is dried by the same drying method to obtain a current collector (structure) on which an active material-containing layer containing moisture of 1000 ppm by mass to 10000 ppm by mass as measured by the Karl Fischer method is formed. The application and drying of the slurry to the other side of the current collector may also be omitted.

[0032] Next, the press S3 will be described. An example of a device used in the press S3 is shown in Figs.

[0033] The manufacturing apparatus 32 of the example of FIG. 9 includes a rolling section and a winding section 40. In the manufacturing apparatus 32, the structure 10 in which the active material-containing layer 3b has been dried is carried into the rolling section. Then, the structure 10 is transported from the rolling section to the winding section 40 through guide rollers 35 to 39 in this order. The winding section 40 winds up the transported structure 10. In the example of FIG. 9, the winding section 40 includes a winding reel, and the structure 10 is wound up in a roll on the winding reel. In the example of FIG. 9, the structure 10 is guided from the upstream side to the downstream side by five guide rollers 35, 36, 37, 38, and 39 between the rolling section and the winding section 40. Each of the guide rollers 35 to 39 is formed of a metal such as iron or stainless steel.

[0034] The rolling section rolls the active material-containing layer 3b in the transported structure 10 by a roll press or the like. As shown in FIG. 10, the rolling section includes a pair of press rollers 33 and 34, each of which is made of a metal such as iron or stainless steel. The press roller 33 presses the active material-containing layer 3b from one side in the thickness direction of the structure 10, and the press roller 34 presses the active material-containing layer 3b from the opposite side to the press roller 33 in the thickness direction of the structure 10. As a result, the active material-containing layer 3b is sandwiched between the press rollers 33 and 34 in the thickness direction of the structure 10, and pressure (press pressure) in the thickness direction of the structure 10 is applied to the active material-containing layer 3b. At this time, when the active material-containing layer 3b is applied to both sides of the current collector 3a, the active material-containing layer 3b is pressed in a state in which each of the press rollers 33 and 34 is in contact with the active material-containing layer 3b. When the active material-containing layer 3b is applied to only one surface of the current collector 3a, the active material-containing layer 3b is pressed with one of the press rollers 33, 34 in contact with the active material-containing layer 3b and the other of the press rollers 33, 34 in contact with the coated region of the current collector 3a. The pressure from the press rollers 33, 34 compresses the active material-containing layer 3b in the thickness direction of the structure 10 and stretches it in the longitudinal direction of the structure 10.

[0035] The rolled structure is wound up by the winding section 40. At this time, a winding tension is applied to the structure 10. Since the surface of the rolled structure is smooth, even if the winding tension is increased, a flat electrode can be formed without transferring unevenness between the two. Furthermore, when the moisture content of the structure is low, it is desirable to reduce the tensile stress in order to avoid breakage. The winding tension can be adjusted in the range of 10N or more and 100N or less. To suppress wrinkles during pressing, it is preferable to apply a winding tension of 30N or more.

[0036] Next, cutting S4 will be described.

[0037] The structure wound into a roll in the previous step is sent out and cut into a predetermined shape by punching with a punching die as shown in FIG. 11. In FIG. 11, the cut sides are indicated by dotted lines. In this way, an electrode 3 having a structure as shown in FIG. 12, for example, is obtained. As shown in FIG. 12, the electrode 3 comprises a rectangular current collector 3a, active material-containing layers 3b provided on both main surfaces of the current collector 3a, and a current collector tab 3c protruding in a rectangular shape from one end of the current collector 3a. The current collector tab 3c is obtained by punching out a portion of the current collector 3a where the active material-containing layer is not formed into a predetermined shape.

[0038] An example of cutting using a punching die is cutting (punching) using a Thomson blade.

[0039] An example of an electrode of a comparative example in which wrinkles 41 were generated in the current collecting tab 3c near the active material-containing layer 3b during pressing is shown in Fig. 13. According to the method of the embodiment, the electrode is unlikely to break even when a large tension is applied during pressing, so that it is possible to prevent wrinkles from being generated in the tab portion.

[0040] It should be noted that cutting S4 is for obtaining a predetermined shape, and therefore can be omitted if the predetermined shape is obtained in the steps up to S3.

[0041] Next, the second drying step S5 will be described.

[0042] In the second drying S5, the structure (or electrode) after the pressing S3 or cutting S4 is laminated in the thickness direction, and both sides of the obtained laminate intersecting the lamination direction are dried while being pressed, so that the moisture content of the active material-containing layer is set to 600 mass ppm or less as measured by the Karl Fischer method. The second drying will be described with reference to Figs. 14 and 15.

[0043] 14 and 15 show a jig used in the second drying. The housing 50 shown in FIG. 14 and FIG. 15 includes a container 51, a cover plate 52, a bottom plate 53, and a spring member 54. In FIG. 14 and FIG. 15, the long side direction of the container 51 is indicated as the y-axis direction, the short side direction of the container 51 is indicated as the x-axis direction, and the depth direction of the container 51 is indicated as the z-axis direction. The container 51 has a rectangular cylindrical shape with a bottom. The bottom plate 53 has the same or approximately the same planar dimensions as a plane along the xy axis surrounded by the inner wall of the container 51. The bottom plate 53 is disposed at a predetermined height in the z-axis direction from the inner bottom surface of the container 51. The spring member 54 is, for example, a coil spring. The spring member 54 is disposed between the inner bottom surface of the container 51 and the bottom plate 53. When the spring member 54 contracts, the position of the bottom plate 53 in the container 51 moves downward along the z-axis direction. Furthermore, when the spring member 54 expands, the position in the container 51 moves upward along the z-axis direction. A plurality of objects (for example, electrodes 3) to be subjected to the second drying S5 are prepared. A plurality of electrodes 3 are used in order to increase production efficiency. A plurality of electrodes 3 are stacked on the bottom plate 53 in the container 51 so that the thickness direction of the electrodes 3 is parallel to the depth direction (z-axis direction) of the container 51. The cover plate 52 is placed at the opening of the container 51. The upper end of the long side direction (y-axis direction) of the opening of the container 51 is bent inwardly, so that the cover plate 52 is fixed to the opening of the container 51. The stack of electrodes 3 is sandwiched between the cover plate 52 and the bottom plate 53. Furthermore, the stack of electrodes 3 receives an upward force along the z-axis direction due to the elastic force of the spring member 54 through the bottom plate 53. Therefore, the stack of electrodes 3 is sandwiched between the cover plate 52 and the bottom plate 53, and both sides are pressurized. This makes it possible to prevent deformation such as warping or curvature from occurring in electrode 3 during the second drying. Note that container 51, cover plate 52, and bottom plate 53 may be made of a metal such as Al or an Al alloy.

[0044] The housing 50 containing the stack of electrodes 3 described above is placed in a drying furnace and subjected to the second drying S5. The second drying S5 is performed so that the moisture content of the electrode 3 according to the Karl Fischer method is 600 mass ppm or less. By making the moisture content 600 mass ppm or less, the hardness of the electrode 3 can be increased. This makes it possible to avoid manufacturing defects such as the electrode dropping, deformation, and inability to transport the electrode to a predetermined position when transporting the electrode to a subsequent process. In addition, when the electrode 3 is the first electrode and a separator is disposed between the first electrode and the second electrode to prepare an electrode group, it is necessary to hold these electrodes by a transport device such as a vacuum and place them in a predetermined position, but since the electrode does not fall from the transport device, it is possible to avoid the electrode being displaced and also to prevent chipping, cracking, etc. from occurring in the electrode. As a result, it is possible to suppress the occurrence of insulation defects in the electrode group.

[0045] Since the occurrence of defects during transportation and the occurrence of insulation defects in the electrode group can be reduced, the production yield can be improved. In addition, making the moisture content 600 ppm by mass or less is useful for improving the performance of a battery equipped with a non-aqueous electrolyte. The lower limit of the moisture content can be set to 50 ppm by mass. By making the moisture content 50 ppm by mass or more, moisture can be left in the pores of the electrode, so that thermal deterioration of the electrode constituent components (e.g., binder) can be avoided and the electrode can be prevented from becoming unnecessarily hard and brittle.

[0046] The drying temperature in the second drying can be in the range of 80°C to 160°C, more preferably 100°C to 140°C. This allows the electrode to be dried to a suitable hardness, so that bending deformation when the electrode area is increased can be suppressed. The drying time can be in the range of, for example, 1 hour to 48 hours, more preferably 6 hours to 24 hours. Here, the drying temperature is, for example, the temperature inside the drying oven.

[0047] The water content of the active material-containing layer as determined by the Karl Fischer method can be adjusted, for example, by the drying temperature, drying time, composition of the active material-containing layer, and the like.

[0048] The second drying can be, for example, vacuum drying or reduced pressure drying.

[0049] A method for measuring the moisture content of the electrode 3 by the Karl Fischer method will be described below. After the second drying S5, the moisture content of each of the three electrodes 3 in the stack of electrodes 3 in the container 51, including the electrode 3 located on each of the outermost layers and the electrode 3 located at the center of the stack, is measured by the Karl Fischer method in the same manner as described for the first drying S2. The average of the three measured values ​​obtained is regarded as the desired value.

[0050] An electrode can be manufactured by a method including the steps described above.

[0051] The electrode manufactured by the method of the embodiment will be described in detail below.

[0052] The electrode may include a current collector and an active material-containing layer. The active material-containing layer may be laminated or formed on one or both sides of the current collector. The active material-containing layer may include an active material and, optionally, a conductive agent and a binder.

[0053] The electrodes can be used as positive or negative electrodes.

[0054] The active material includes at least one of a niobium-containing oxide and a titanium-containing oxide. Examples of the niobium-containing oxide include a monoclinic niobium-containing oxide and a niobium titanium-containing oxide. Examples of the monoclinic niobium-containing oxide include Nb2TiO7, Nb2Ti2O9, and Nb 10 Ti2O 29 , Nb 14 TiO 37 , Nb 24 TiO 62The niobium titanium-containing oxide may be a substituted niobium titanium composite oxide in which at least a part of Nb and / or Ti is substituted with a different element. Examples of the substituted element include Na, K, Ca, Co, Ni, Si, P, V, Cr, Mo, Ta, Zr, Mn, Fe, Mg, B, Pb, and Al. The substituted niobium titanium composite oxide may contain one type of substituted element, or may contain two or more types of substituted elements. The active material particles may contain one type of niobium-containing oxide, or may contain multiple types of niobium-containing oxide. The niobium-containing oxide preferably contains Nb2TiO7 having a monoclinic structure. In this case, an electrode having excellent capacity and rate performance can be obtained.

[0055] Examples of monoclinic niobium titanium oxides include Li x Ti 1-y M1 y Nb 2-z M2 z O 7+δ Here, M1 is at least one selected from the group consisting of Zr, Si, and Sn. M2 is at least one selected from the group consisting of V, Ta, and Bi. The subscripts in the composition formula are 0≦x≦5, 0≦y<1, 0≦z<2, and -0.3≦δ≦0.3.

[0056] Other examples of monoclinic niobium titanium oxides include Ti 1-y M3 y+z Nb 2-z O 7-δ Here, M3 is at least one selected from Mg, Fe, Ni, Co, W, Ta, and Mo. The subscripts in the composition formula are 0≦y<1, 0≦z<2, and -0.3≦δ≦0.3.

[0057] Another example of a monoclinic niobium titanium oxide is Li a TiM b Nb 2±β O 7±σ(0≦a≦5, 0≦b≦0.3, 0≦β≦0.3, 0≦σ≦0.3, M is at least one element selected from the group consisting of Fe, V, Mo and Ta).

[0058] The niobium-containing oxide may contain unavoidable impurities, examples of which include K, Na, Si, and P.

[0059] The niobium-containing oxide may contain lithium ions by charging, or may be synthesized as a niobium-containing oxide containing lithium by using a compound containing lithium such as lithium carbonate as a starting material for the niobium-containing oxide.

[0060] Titanium-containing oxides include, for example, titanium dioxide with a monoclinic structure, titanium dioxide with a rutile structure, and titanium dioxide with an anatase structure. Titanium dioxide with each crystal structure has a composition of TiO2 before charging and a composition of LiO2 after charging. x It can be expressed as TiO2 (x is 0≦x≦1). In addition, the structure of titanium dioxide with a monoclinic crystal structure before charging can be expressed as TiO2(B).

[0061] The titanium-containing oxide may contain unavoidable impurities, such as K, Na, Cs, Ba, Ca, Si, and P.

[0062] The niobium-containing oxide and the titanium-containing oxide desirably do not contain lithium when mixed with a solvent containing water to be described later and contained in a slurry, which prevents the slurry from becoming alkaline, thereby suppressing deterioration of the current collector.

[0063] The type of active material used may be one or more. The active material may also contain a second active material other than the niobium-containing oxide and the titanium-containing oxide. An example of the second active material is lithium titanate having a ramsdellite structure (e.g., Li 2+y Ti3O7, 0≦y≦3), lithium titanates with spinel structure (e.g., Li 4+xTi5O 12 , 0≦x≦3), hollandite-type titanium composite oxide, and orthorhombic titanium composite oxide.

[0064] The active material may be in the form of particles, which may be, for example, primary particles alone, secondary particles formed by agglomeration of primary particles, or a mixture of primary particles and secondary particles.

[0065] The conductive agent is blended to improve the current collecting performance and to reduce the contact resistance between the active material and the current collector. Examples of the conductive agent include vapor grown carbon fiber (VGCF), carbon nanotubes, carbon black such as acetylene black, and carbonaceous materials such as graphite. One of these may be used as the conductive agent, or two or more may be used in combination as the conductive agent. Alternatively, instead of using a conductive agent, a carbon coating or an electronically conductive inorganic material coating may be applied to the surface of the active material particles.

[0066] The binder can fill the gaps between the active material and can bind the active material and the current collector. The binder has affinity with the water-containing solvent and can be dispersed or dissolved in the water-containing solvent. Examples of the binder include carboxymethyl cellulose (CMC) and a salt of CMC. Examples of the salt of CMC include a sodium salt of CMC and a potassium salt of CMC. One of these may be used as the binder, or two or more may be used in combination as the binder. The binder containing CMC and / or a salt of CMC can cover the surface of the niobium-containing oxide particles, and therefore can suppress the reaction between the niobium-containing oxide particles and the electrolyte.

[0067] Styrene-butadiene rubber may be added to the binder containing CMC and / or a salt of CMC, thereby improving the binding strength between the active material-containing layer and the current collector.

[0068] The water-containing solvent may be water alone or a polar solvent containing water.

[0069] The active material-containing layer may contain a solid electrolyte. The lithium ion conductivity of the solid electrolyte is, for example, 1×10 -6 Scm -1 Examples of the lithium ion conductive solid electrolyte include a lithium ion conductive oxide-based solid electrolyte and a lithium ion conductive sulfide-based solid electrolyte. Examples of the lithium ion conductive oxide-based solid electrolyte include a lithium phosphate solid electrolyte with a NASICON structure, an amorphous LIPON (Li 2.9 PO 3.3 N 0.46 ), or garnet-type structure LLZ (Li7La3Zr2O 12 ) etc.

[0070] As an example, the active material, conductive agent, and binder in the active material-containing layer are preferably mixed in proportions of 68% by mass or more and 96% by mass or less, 2% by mass or more and 30% by mass or less, and 2% by mass or more and 30% by mass or less, respectively. By making the amount of conductive agent 2% by mass or more, the current collection performance of the active material-containing layer can be improved. Also, by making the amount of binder 2% by mass or more, the binding between the active material-containing layer and the current collector becomes sufficient, and excellent cycle performance can be expected. On the other hand, it is preferable to make the conductive agent and binder 30% by mass or less each in order to increase capacity.

[0071] The current collector is made of a material that is electrochemically stable at the potential at which lithium (Li) is inserted into and extracted from the active material. One example of the current collector is copper, nickel, stainless steel, or aluminum, or an aluminum alloy containing one or more elements selected from Mg, Ti, Zn, Mn, Fe, Cu, and Si. The thickness of the current collector is preferably 5 μm or more and 20 μm or less. A current collector having such a thickness can balance the strength and weight of the electrode.

[0072] The current collector may also include a portion on the surface of which no active material-containing layer is formed, and this portion can function as a current collecting tab.

[0073] According to the method of the first embodiment described above, the structure is laminated in a thickness direction, and both sides of the obtained laminate intersecting the lamination direction are dried while applying pressure, so that the moisture content of the active material-containing layer is 600 mass ppm or less as measured by the Karl Fischer method. As a result, the occurrence of defects during transportation and insulation defects in the electrode group can be reduced, thereby improving the production yield. Second Embodiment The second embodiment relates to a method for manufacturing a battery.

[0074] The second embodiment includes a step of preparing an electrode group by using the electrode obtained by the method of the first embodiment as a first electrode and disposing a separator between the first electrode and a second electrode; A step of housing the electrode group in an exterior member; and retaining a non-aqueous electrolyte in the electrode group housed in the exterior member.

[0075] The method of the second embodiment includes steps S6 to S9 shown in FIG.

[0076] The electrode group preparation step S6 will now be described.

[0077] The electrode group is produced, for example, by disposing a separator between a first electrode and a second electrode. The shape of the electrode group is not particularly limited, and may be, for example, a stack of the first electrode, the separator, and the second electrode, a flat or cylindrically wound first electrode, a zigzag first electrode, the separator, and the second electrode, or the like.

[0078] The second electrode and the separator will now be described.

[0079] The second electrode can include a second current collector and a second active material-containing layer. The second active material-containing layer can be formed on one or both sides of the second current collector. The second active material-containing layer can include a second active material, and optionally a conductive agent and a binder. The second electrode can be either a positive electrode or a negative electrode, but when the first electrode is a negative electrode, it can be a positive electrode.

[0080] As the second active material, for example, an oxide or a sulfide can be used. The second electrode may contain a single compound as the active material, or may contain a combination of two or more compounds. Examples of oxides and sulfides include compounds into which Li or Li ions can be inserted and desorbed.

[0081] Examples of such compounds include, for example, manganese dioxide (MnO2), iron oxide, copper oxide, nickel oxide, lithium manganese composite oxide (for example, Li x Mn2O4 or Li x MnO2; 0 < x ≦ 1), lithium nickel composite oxide (for example, Li x NiO2; 0 < x ≦ 1), lithium cobalt composite oxide (for example, Li x CoO2; 0 < x ≦ 1), lithium nickel cobalt composite oxide (for example, Li x Ni 1-y Co y O2; 0 < x ≦ 1, 0 < y < 1), lithium manganese cobalt composite oxide (for example, Li x Mn y Co 1-y O2; 0 < x ≦ 1, 0 < y < 1), lithium manganese nickel composite oxide having a spinel structure (for example, Li x Mn 2-y Ni y O4; 0 < x ≦ 1, 0 < y < 2), lithium phosphate having an olivine structure (for example, Li x FePO4; 0 < x ≦ 1, Li x Fe 1-y Mn y PO4; 0 < x ≦ 1, 0 < y ≦ 1, Li x CoPO4; 0 < x ≦ 1), iron sulfate (Fe2(SO4)3), vanadium oxide (for example, V2O5), LiNix Co y M z O2 (where x + y + z = 1, x ≥ 0.8, and M consists of Mn and Al), and lithium nickel cobalt manganese composite oxide (Li x Ni 1-y-z Co y Mn z O2; 0 < x ≤ 1, 0 < y < 1, 0 < z < 1, y + z < 1) is included.

[0082] The primary particle size of the second active material is preferably 100 nm or more and 1 μm or less. The second active material with a primary particle size of 100 nm or more is easy to handle in industrial production. The second active material with a primary particle size of 1 μm or less can allow the solid-state diffusion of lithium ions to proceed smoothly.

[0083] The specific surface area of the second active material is preferably 0.1 m 2 / g or more and 10 m 2 / g or less. The second active material with a specific surface area of 0.1 m 2 / g or more can sufficiently secure the Li-ion insertion / extraction sites. The second active material with a specific surface area of 10 m 2 / g or less is easy to handle in industrial production and can ensure good charge-discharge cycle performance.

[0084] The binder is formulated to fill the gaps between the dispersed second active materials and to bind the second active material and the second current collector. Examples of the binder include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine rubber, polyacrylic acid compounds, imide compounds, carboxymethyl cellulose (CMC), and salts of CMC. One of these may be used as the binder, or two or more of them may be combined and used as the binder.

[0085] The conductive agent is blended to improve current collection performance and reduce contact resistance between the second active material and the second current collector. Examples of the conductive agent include vapor grown carbon fiber (VGCF), carbon black such as acetylene black, and carbonaceous materials such as graphite. One of these may be used as the conductive agent, or two or more may be used in combination as the conductive agent. The conductive agent may also be omitted.

[0086] In the second active material-containing layer, the second active material and the binder are preferably mixed in proportions of 80% by mass or more and 98% by mass or less and 2% by mass or more and 20% by mass or less, respectively.

[0087] By making the amount of binder 2% by mass or more, sufficient electrode strength can be obtained. In addition, the binder can function as an insulator. Therefore, by making the amount of binder 20% by mass or less, the amount of insulator contained in the electrode is reduced, and the internal resistance can be reduced.

[0088] When a conductive agent is added, the second active material, binder, and conductive agent are preferably mixed in proportions of 77% by mass or more and 95% by mass or less, 2% by mass or more and 20% by mass or less, and 3% by mass or more and 15% by mass or less, respectively.

[0089] By making the amount of the conductive agent 3% by mass or more, the above-mentioned effects can be achieved. Also, by making the amount of the conductive agent 15% by mass or less, the ratio of the conductive agent in contact with the electrolyte can be reduced. If this ratio is low, decomposition of the electrolyte during high-temperature storage can be reduced.

[0090] The second current collector is preferably an aluminum foil or an aluminum alloy foil containing one or more elements selected from Mg, Ti, Zn, Ni, Cr, Mn, Fe, Cu and Si.

[0091] The thickness of the aluminum foil or aluminum alloy foil is preferably 5 μm or more and 20 μm or less, more preferably 15 μm or less. The purity of the aluminum foil is preferably 99 mass% or more. The content of transition metals such as iron, copper, nickel, and chromium contained in the aluminum foil or aluminum alloy foil is preferably 1 mass% or less.

[0092] The second current collector may also include a portion on the surface of which the second active material-containing layer is not formed, and this portion may function as a second current collecting tab.

[0093] For example, the second electrode is prepared by suspending the second active material, the conductive agent, and the binder in a solvent to prepare a slurry. The slurry is then applied to one or both sides of a current collector. The applied slurry is then dried to obtain a laminate of an active material-containing layer and a current collector. Then, the laminate is pressed. In this manner, the second electrode is prepared. Alternatively, the second electrode may be prepared by the following method. First, the active material, the conductive agent, and the binder are mixed to obtain a mixture. Then, the mixture is formed into pellets. Then, the pellets are placed on the current collector to obtain the second electrode.

[0094] The separator is formed, for example, from a porous film containing polyethylene (PE), polypropylene (PP), cellulose, or polyvinylidene fluoride (PVdF), or a synthetic resin nonwoven fabric. From the viewpoint of safety, it is preferable to use a porous film formed from polyethylene or polypropylene. This is because these porous films melt at a certain temperature and are capable of cutting off electric current.

[0095] The separator may be an electrolyte layer containing a solid electrolyte. The lithium ion conductivity of the solid electrolyte is, for example, 1x10 -6 Scm -1Examples of the lithium ion conductive solid electrolyte include a lithium ion conductive oxide-based solid electrolyte and a lithium ion conductive sulfide-based solid electrolyte. Examples of the lithium ion conductive oxide-based solid electrolyte include a lithium phosphate solid electrolyte with a NASICON structure, an amorphous LIPON (Li 2.9 PO 3.3 N 0.46 ), or garnet-type structure LLZ (Li7La3Zr2O 12 ) etc.

[0096] Next, step S7 of housing the electrode group in an exterior member will be described.

[0097] The electrode group is housed in an exterior member. The exterior member is not sealed and is left in an open state. Before the housing, current collecting leads may be electrically connected to the first electrode and the second electrode of the electrode group.

[0098] As the exterior member, for example, a container made of a laminate film or a metal container can be used.

[0099] The thickness of the laminate film is, for example, 0.5 mm or less, preferably 0.2 mm or less.

[0100] The laminate film is a multi-layer film including a plurality of resin layers and a metal layer interposed between the resin layers. The resin layers include polymeric materials such as polypropylene (PP), polyethylene (PE), nylon, and polyethylene terephthalate (PET). The metal layer is preferably made of aluminum foil or aluminum alloy foil for weight reduction. The laminate film can be molded into the shape of the exterior member by sealing it by heat fusion.

[0101] The thickness of the wall of the metal container is, for example, 1 mm or less, more preferably 0.5 mm or less, and even more preferably 0.2 mm or less.

[0102] The metal container is made of, for example, aluminum or an aluminum alloy. The aluminum alloy preferably contains elements such as magnesium, zinc, and silicon. When the aluminum alloy contains transition metals such as iron, copper, nickel, and chromium, the content of the transition metals is preferably 100 ppm by mass or less.

[0103] The shape of the exterior member is not particularly limited. The shape of the exterior member may be, for example, flat (thin), rectangular, cylindrical, coin, or button. The exterior member can be appropriately selected depending on the battery dimensions and the application of the battery.

[0104] The current collecting lead can be formed, for example, from a conductive material, such as the same type of material as the current collector of the electrode or the current collector of the second electrode.

[0105] The electrode group housed in the exterior member may be dried at a temperature of 80° C. or more and 150° C. or less. The drying step is carried out on the exterior member while it is still unsealed.

[0106] By setting the drying temperature in the range of 80° C. to 150° C., it is possible to remove moisture contained in the electrode group without thermally deteriorating the materials contained in the electrode group. When the drying temperature is 80° C. to 150° C., the drying time can be, for example, 1 hour to 72 hours. In addition, when the electrode group has reached an appropriate moisture content by the second drying step S5, the drying step in the state where the electrode group is housed in the exterior member may be omitted, thereby enabling the tact time to be reduced.

[0107] Next, step S8 of housing the electrolyte in the exterior member will be described.

[0108] The electrolyte is retained in the electrode group while the exterior member is left in an open state. The retaining step is carried out, for example, in a dehumidified atmosphere or in dry air.

[0109] Examples of the electrolyte include non-aqueous electrolytes and aqueous electrolytes. For example, liquid non-aqueous electrolytes or gel non-aqueous electrolytes can be used as the non-aqueous electrolyte. The liquid non-aqueous electrolyte is prepared by dissolving an electrolyte salt as a solute in an organic solvent. The concentration of the electrolyte salt is preferably 0.5 mol / L or more and 2.5 mol / L or less.

[0110] Examples of the electrolyte salt include lithium salts such as lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), and lithium bistrifluoromethylsulfonylimide (LiN(CF3SO2)2), and mixtures thereof. The electrolyte salt is preferably one that is difficult to oxidize even at high potentials, and LiPF6 is most preferred.

[0111] Examples of organic solvents include cyclic carbonates such as propylene carbonate (PC), ethylene carbonate (EC), and vinylene carbonate (VC); chain carbonates such as diethyl carbonate (DEC), dimethyl carbonate (DMC), and methyl ethyl carbonate (MEC); cyclic ethers such as tetrahydrofuran (THF), 2-methyl tetrahydrofuran (2MeTHF), and dioxolane (DOX); chain ethers such as dimethoxyethane (DME) and diethoxyethane (DEE); γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane (SL). These organic solvents can be used alone or as a mixed solvent.

[0112] The gelled non-aqueous electrolyte is prepared by combining a liquid non-aqueous electrolyte with a polymeric material, such as polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyethylene oxide (PEO), or a mixture thereof.

[0113] Alternatively, as the nonaqueous electrolyte, in addition to liquid nonaqueous electrolytes and gel nonaqueous electrolytes, room temperature molten salts containing lithium ions (ionic melts), polymer solid electrolytes, inorganic solid electrolytes, and the like may be used.

[0114] Room temperature molten salts (ionic melts) refer to organic salts consisting of a combination of organic cations and anions that can exist as a liquid at room temperature (15°C or higher and 25°C or lower). Room temperature molten salts include room temperature molten salts that exist as a liquid by themselves, room temperature molten salts that become liquid when mixed with an electrolyte salt, room temperature molten salts that become liquid when dissolved in an organic solvent, and mixtures of these. In general, the melting point of room temperature molten salts used in secondary batteries is 25°C or lower. In addition, organic cations generally have a quaternary ammonium skeleton.

[0115] The polymer solid electrolyte is prepared by dissolving an electrolyte salt in a polymer material and solidifying it.

[0116] The inorganic solid electrolyte is a solid substance having Li-ion conductivity. The lithium ion conductivity of the solid electrolyte is, for example, 1x10 at 25°C. -6 Scm -1 Examples of the lithium ion conductive solid electrolyte are as described above.

[0117] Next, sealing S9 will be described.

[0118] The exterior member is sealed to obtain a battery. The sealing method varies depending on the type of exterior member. For example, in the case of a container made of a laminate film, heat sealing can be used. In addition, in the case of a metal container, laser welding can be used.

[0119] Examples of batteries that can be manufactured by the method according to the embodiment are shown in FIGS.

[0120] 16 and 17 show examples of batteries equipped with a stacked electrode group.

[0121] 16 and 17 includes an electrode group 1 shown in Fig. 16 and 17, an exterior member 2 shown in Fig. 16, and a non-aqueous electrolyte (not shown). The electrode group 1 and the non-aqueous electrolyte are housed in the exterior member 2. The non-aqueous electrolyte is held in the electrode group 1.

[0122] The exterior member 2 is made of a laminate film including two resin layers and a metal layer interposed between them.

[0123] The electrode group 1 is a laminated type electrode group, as shown in Fig. 17. The laminated type electrode group 1 has a structure in which negative electrodes 3 and positive electrodes 5 are alternately laminated with separators 4 interposed therebetween.

[0124] The electrode group 1 includes a plurality of negative electrodes 3. Each of the plurality of negative electrodes 3 includes a negative electrode current collector 3a and a negative electrode active material-containing layer 3b supported on both sides of the negative electrode current collector 3a. The electrode group 1 also includes a plurality of positive electrodes 5. Each of the plurality of positive electrodes 5 includes a positive electrode current collector 5a and a positive electrode active material-containing layer 5b supported on both sides of the positive electrode current collector 5a.

[0125] The negative electrode current collector 3a of each negative electrode 3 includes a portion 3c on one side of which the negative electrode active material-containing layer 3b is not supported on any surface. This portion 3c serves as a negative electrode current collector tab. The portion 3c serving as a negative electrode current collector tab does not overlap with the positive electrode 5. In addition, the multiple negative electrode current collector tabs (portions 3c) are electrically connected to a strip-shaped negative electrode terminal 6. The tip of the strip-shaped negative electrode terminal 6 is pulled out to the outside of the exterior member 2.

[0126] Although not shown, the positive electrode current collector 5a of each positive electrode 5 includes a portion on one side where the positive electrode active material-containing layer 5b is not supported on any surface. This portion serves as a positive electrode current collector tab. The positive electrode current collector tab does not overlap with the negative electrode 3, similar to the negative electrode current collector tab (portion 3c). The positive electrode current collector tab is located on the opposite side of the electrode group 1 to the negative electrode current collector tab (portion 3c). The positive electrode current collector tab is electrically connected to a strip-shaped positive electrode terminal 7. The tip of the strip-shaped positive electrode terminal 7 is located on the opposite side to the negative electrode terminal 6, and is drawn out to the outside of the exterior member 2.

[0127] The laminated electrode group is not limited to the structure shown in FIG. 17. Another example of the laminated electrode group 1 is shown in FIG. 18. A positive electrode 5, a negative electrode 3, a positive electrode 5, and a negative electrode 3 are arranged in this order so as to be sandwiched between the separators 4 folded in a zigzag pattern. A positive electrode current collecting tab 5c protrudes from one long side of the separator 4 folded in a zigzag pattern. A negative electrode current collecting tab (not shown) protrudes from the other long side of the separator 4 folded in a zigzag pattern. The order of the positive electrode 5 and the negative electrode 3 is not limited to that shown in FIG. 18, and may be the negative electrode 3 and the positive electrode 5.

[0128] 19 and 20 show examples of batteries equipped with a wound electrode group.

[0129] 19 and 20 includes a bag-shaped exterior member 2 shown in Fig. 19 and 20, an electrode group 1 shown in Fig. 19, and an electrolyte (not shown). The electrode group 1 and the non-aqueous electrolyte are stored in the bag-shaped exterior member 2. The non-aqueous electrolyte (not shown) is held in the electrode group 1.

[0130] The bag-shaped exterior member 2 is made of a laminate film including two resin layers and a metal layer interposed between them.

[0131] As shown in Fig. 19, the electrode group 1 is a flat wound-type electrode group. As shown in Fig. 20, the flat wound-type electrode group 1 includes a negative electrode 3, a separator 4, and a positive electrode 5. The separator 4 is interposed between the negative electrode 3 and the positive electrode 5.

[0132] The negative electrode 3 includes a negative electrode current collector 3a and a negative electrode active material-containing layer 3b. In the negative electrode 3, in a portion located at the outermost shell of the wound-type electrode group 1, the negative electrode active material-containing layer 3b is formed only on the inner surface side of the negative electrode current collector 3a as shown in Fig. 20. In the other portions of the negative electrode 3, the negative electrode active material-containing layer 3b is formed on both sides of the negative electrode current collector 3a.

[0133] The positive electrode 5 includes a positive electrode current collector 5a and a positive electrode active material-containing layer 5b formed on both sides of the positive electrode current collector 5a.

[0134] As shown in Fig. 19, the negative electrode terminal 6 and the positive electrode terminal 7 are located near the outer peripheral end of the wound electrode group 1. The negative electrode terminal 6 is connected to a portion located at the outermost shell of the negative electrode current collector 3a. The positive electrode terminal 7 is connected to a portion located at the outermost shell of the positive electrode current collector 5a. The negative electrode terminal 6 and the positive electrode terminal 7 extend to the outside from an opening of the bag-shaped exterior member 2. A thermoplastic resin layer is provided on the inner surface of the bag-shaped exterior member 2, and the opening is closed by heat sealing.

[0135] The battery manufactured by the method of the second embodiment may be used as a battery pack or may be incorporated into a battery pack. The battery according to the embodiment is preferably used in applications requiring excellent cycle performance when a large current is drawn. Specifically, the battery is used as a power source for digital cameras, or as a vehicle battery for, for example, two- to four-wheeled hybrid electric vehicles, two- to four-wheeled electric vehicles, power-assisted bicycles, or railroad cars (e.g., trains), or as a stationary battery. In particular, the battery is preferably used as an on-board battery mounted on a vehicle.

[0136] According to the second embodiment described above, a battery is manufactured using the electrode manufactured by the method of the first embodiment. As a result, defects during electrode manufacturing can be reduced, and the yield of battery manufacturing can be improved. EXAMPLES

[0137] Examples will be described below. <Example 1> As the active material, particles of monoclinic niobium titanium-containing oxide having a composition represented by the formula TiNb2O7 were prepared. In addition, acetylene black was prepared as a conductive agent, and carboxymethyl cellulose and styrene butadiene rubber were prepared as binders. These were mixed in pure water so that the mass ratio of active material: acetylene black: carboxymethyl cellulose: styrene butadiene rubber was 90: 5: 2.5: 2.5 to obtain a slurry. This slurry was applied to one side of a belt-shaped current collector made of aluminum foil having a thickness of 12 μm, except for both ends in the short side direction, and the coating was dried for 240 seconds in a drying oven set at 60 ° C. During this first drying, the active material-containing layer-free parts located at both ends in the short side direction of the current collector were sandwiched between the guide roller 28 and the conveying roller 29 shown in FIG. 6, and the first drying was performed.

[0138] In addition, the winding tension of the structure after one-side coating was completed was adjusted to 10 N against the aluminum current collector. This makes it possible to prevent the semi-dried structures from transferring to each other. After one-side coating was completed, the slurry was applied to the uncoated side of the strip-shaped current collector in the same manner. In this way, a structure having an active material-containing layer formed on both sides of the strip-shaped current collector except for both ends in the short side direction was obtained with a length of 400 m. The structure was wound into a roll. The moisture content of the active material-containing layer of the structure was measured by the Karl Fischer method using the method described above, and the results are shown in Table 1. Next, the obtained structure was rolled up so that the density of the active material-containing layer was 2.65 g / cm. 3 The electrode was subjected to roll pressing so that the initial tensile tension was 100N, and pressing was performed at a speed of 1m per minute. If breakage occurred during pressing, the tensile tension was reduced by 10N at a time, and the tension at which the electrode did not break per 100m of rolling distance was determined, and the electrode pressed at that tension was subjected to the next process. The tension during pressing was 80N.

[0139] The obtained electrode was punched out into 50 pieces in the electrode shape shown in FIG. 12 using a puncher with a Thomson blade to prepare the electrode of Example 1. In the electrode of Example 1, the long side of the active material-containing layer was 150 mm long, and the short side of the active material-containing layer was 60 mm long. The width of the current collecting tab (width parallel to the short side of the active material-containing layer) was 30 mm. The length of the current collecting tab (width parallel to the long side of the active material-containing layer) was 10 mm. The outer periphery of the electrode of Example 1 was observed with a stereomicroscope, and electrodes in which cracks in the active material-containing layer, cracks in the current collector, peeling of the active material-containing layer, or deformation or peeling due to wrinkles in the current collecting tab were observed were determined to be defective cuts. The number of defective cuts was zero.

[0140] One hundred electrodes prepared by the method of Example 1 were used as negative electrodes. These negative electrodes were inserted into container 51 of case 50 shown in Fig. 14 and Fig. 15, sandwiched between cover plate 52 and bottom plate 53, and vacuum dried at 140°C for 12 hours. After drying, the moisture contents of the negative electrodes located at the top and bottom outermost layers of the electrode stack and three negative electrodes located at the center were measured by Karl Fischer using the method described above, and the average value was calculated and shown in Table 1.

[0141] Next, lithium cobalt oxide (LiCoO2) particles were prepared as the positive electrode active material. In addition, acetylene black was prepared as the conductive agent, and PVdF was prepared as the binder. These were dispersed in N-methyl-2-pyrrolidone (NMP) so that the mass ratio of active material: acetylene black: PVdF was 90:5:5 to obtain a slurry. This slurry was applied to both sides of a current collector made of 12 μm aluminum foil, and the coating was dried at 100° C. for 240 seconds. In this way, a laminate in which an active material-containing layer was formed on both sides of the current collector was obtained. Next, the obtained laminate was placed in a container having an active material-containing layer with a density of 2.2 g / cm. 3 The positive electrode roll was subjected to a roll press so that the positive electrode roll was obtained. The positive electrode roll obtained was punched out into a shape of 58 mm × 148 mm to prepare 90 positive electrodes.

[0142] A laminated electrode group was produced using the positive and negative electrodes and the polyethylene separator produced as described above. The positive and negative electrodes were set in an electrode laminate production device. The positive and negative electrodes were transported by a vacuum chuck of the laminate production device, and the polyethylene separator was sandwiched between the positive and negative electrodes in a zigzag shape to obtain a flat laminated electrode group. Thus, 10 sets of electrode laminates with 9 positive electrodes and 10 negative electrodes were produced. A positive electrode terminal and a negative electrode terminal were connected to this electrode group. In order to confirm the insulation of this laminated electrode group, an insulation resistance test was performed using an insulation resistance tester. When a direct current of 600 V was applied and the resistance was 5 MΩ or more, the test was considered to have passed. All 10 sets passed. Therefore, no internal short circuit was observed in the produced electrode group. The number of internal short circuits is shown in Table 1. <Example 2> The drying temperature of the slurry (temperature of the drying oven in the first drying) and the drying time were changed as shown in Table 1 below, and the moisture content of the active material-containing layer measured by the Karl Fischer method was changed as shown in Table 1 below. Except for this, 100 negative electrodes were manufactured in the same manner as in Example 1. When the number of cutting defects occurred for the obtained negative electrode of Example 2 in the same manner as in Example 1, it was zero.

[0143] These negative electrodes were inserted into container 51 of housing 50, sandwiched between cover plate 52 and bottom plate 53, and vacuum dried at 140° C. for 48 hours. After drying, the moisture contents of the negative electrodes located in the upper and lower outermost layers of the electrode stack and three negative electrodes located in the center were measured by the Karl Fischer method using the method described above, and the average values ​​were calculated and shown in Table 1.

[0144] Next, 90 positive electrodes were produced in the same manner as in Example 1.

[0145] A laminated electrode group was produced using the positive and negative electrodes and the polyethylene separator produced as described above. The positive and negative electrodes were set in an electrode laminate production device. The positive and negative electrodes were transported by a vacuum chuck of the laminate production device, and the polyethylene separator was sandwiched between the positive and negative electrodes in a zigzag shape to obtain a flat laminated electrode group. Thus, 10 sets of electrode laminates with 9 positive electrodes and 10 negative electrodes were produced. A positive electrode terminal and a negative electrode terminal were connected to this electrode group. In order to confirm the insulation of this laminated electrode group, an insulation resistance test was performed using an insulation resistance tester. When a direct current of 600 V was applied and the resistance was 5 MΩ or more, the test was considered to have passed. All 10 sets passed. Therefore, no internal short circuit was observed in the produced electrode group. The number of internal short circuits is shown in Table 1. <Example 3> The drying temperature of the slurry (temperature of the drying oven in the first drying) and the drying time were changed as shown in Table 1 below, and the moisture content of the active material-containing layer measured by the Karl Fischer method was changed as shown in Table 1 below. Except for this, 100 negative electrodes were manufactured in the same manner as in Example 1. When the number of cutting defects occurred for the obtained negative electrode of Example 3 in the same manner as in Example 1, it was zero.

[0146] These negative electrodes were inserted into container 51 of housing 50, sandwiched between cover plate 52 and bottom plate 53, and vacuum dried at 140° C. for 24 hours. After drying, the moisture contents of the negative electrodes located in the upper and lower outermost layers of the electrode stack and three negative electrodes located in the center were measured by the Karl Fischer method using the method described above, and the average values ​​were calculated and shown in Table 1.

[0147] Next, 90 positive electrodes were produced in the same manner as in Example 1.

[0148] A laminated electrode group was produced using the positive and negative electrodes and the polyethylene separator produced as described above. The positive and negative electrodes were set in an electrode laminate production device. The positive and negative electrodes were transported by a vacuum chuck of the laminate production device, and the polyethylene separator was sandwiched between the positive and negative electrodes in a zigzag shape to obtain a flat laminated electrode group. Thus, 10 sets of electrode laminates with 9 positive electrodes and 10 negative electrodes were produced. A positive electrode terminal and a negative electrode terminal were connected to this electrode group. In order to confirm the insulation of this laminated electrode group, an insulation resistance test was performed using an insulation resistance tester. When a direct current of 600 V was applied and the resistance was 5 MΩ or more, the test was considered to have passed. All 10 sets passed. Therefore, no internal short circuit was observed in the produced electrode group. The number of internal short circuits is shown in Table 1. <Comparative Example 1> The drying temperature of the slurry (temperature of the drying oven in the first drying) and the drying time were changed as shown in Table 1 below, and the moisture content of the active material-containing layer measured by the Karl Fischer method was changed as shown in Table 1 below. Except for this, 100 negative electrodes were manufactured in the same manner as in Example 1. The number of cutting defects of the obtained negative electrode of Comparative Example 1 was measured in the same manner as in Example 1, and was zero.

[0149] These negative electrodes were inserted into container 51 of housing 50, sandwiched between cover plate 52 and bottom plate 53, and vacuum dried at 140° C. for 20 hours. After drying, the moisture contents of the negative electrodes located in the upper and lower outermost layers of the electrode laminate and three negative electrodes located in the center were measured by the Karl Fischer method using the method described above, and the average values ​​were calculated and shown in Table 1.

[0150] Next, 90 positive electrodes were produced in the same manner as in Example 1.

[0151] A laminated electrode group was produced using the positive and negative electrodes and the polyethylene separator produced as described above. The positive and negative electrodes were set in an electrode laminate production device. The positive and negative electrodes were transported by a vacuum chuck of the laminate production device, and the polyethylene separator was sandwiched between the positive and negative electrodes in a zigzag shape to obtain a flat laminated electrode group. Thus, 10 sets of electrode laminates with 9 positive electrodes and 10 negative electrodes were produced. A positive electrode terminal and a negative electrode terminal were connected to this electrode group. In order to confirm the insulation of this laminated electrode group, an insulation resistance test was performed using an insulation resistance tester. When a direct current of 600 V was applied and the resistance was 5 MΩ or more, the electrode group was considered to have passed. Seven of the 10 sets passed. The number of internal short circuits is shown in Table 1. <Comparative Example 2> A battery of Comparative Example 2 was produced without carrying out the first drying and the second drying.

[0152] A slurry having the same composition as in Example 1 was applied to both sides of a strip-shaped current collector made of aluminum foil having a thickness of 12 μm, except for both ends in the short side direction, and the slurry was dried at 100° C. The resulting structure had an active material-containing layer with a density of 2.65 g / cm 3 The electrode was subjected to roll pressing so that the moisture content of the active material-containing layer was set to 2000 mass ppm by the Karl Fischer method by humidifying the electrode in an environment with a dew point of 40° C. for 120 hours after pressing. The electrode thus obtained was punched out into 100 pieces with the same electrode shape as in Example 1 using a punching tool with a Thomson blade to prepare the negative electrode of Comparative Example 2.

[0153] Next, 90 positive electrodes were produced in the same manner as in Example 1.

[0154] A laminated electrode group was produced using the positive and negative electrodes and the polyethylene separator produced as described above. The positive and negative electrodes were set in an electrode laminate production device. The positive and negative electrodes were transported by a vacuum chuck of the laminate production device, and the polyethylene separator was sandwiched between the positive and negative electrodes in a zigzag shape to obtain a flat laminated electrode group. Thus, 10 sets of electrode laminates with 9 positive electrodes and 10 negative electrodes were produced. A positive electrode terminal and a negative electrode terminal were connected to this electrode group. In order to confirm the insulation of this laminated electrode group, an insulation resistance test was performed using an insulation resistance tester. When a direct current of 600 V was applied and the resistance was 5 MΩ or more, it was considered to have passed. Eight of the 10 sets passed. The number of internal short circuits is shown in Table 1.

[0155] [Table 1]

[0156] As shown in Table 1, the methods of Examples 1 to 3 provide a negative electrode with appropriate hardness, which can prevent insulation defects from occurring in the laminated electrode group. Furthermore, the methods of Examples 1 to 3 press the active material-containing layer in a water-containing state, so that the electrode is less likely to break even if a large tension is applied during pressing. The tension press can suppress the curvature of the electrode after pressing, which can suppress distortion of the coated and uncoated parts, thereby reducing cutting defects. Furthermore, as in Examples 1 to 3, by performing curvature correction during drying of the slurry (first drying), the effect of suppressing cutting defects can be further enhanced.

[0157] On the other hand, in the method of Comparative Example 1, since the moisture content after the second drying was more than 600 ppm, the negative electrode sagged during stacking, causing stack position shifting, and an internal short circuit due to poor insulation was confirmed.

[0158] In addition, according to the method of Comparative Example 2, since the negative electrode was humidified after pressing, the obtained negative electrode sagged during stacking, causing a shift in stack position, and an internal short circuit due to poor insulation was confirmed. Furthermore, in Comparative Example 2, the electrode was exposed to a dew point environment after pressing to absorb water, making it difficult for cutting defects to occur, but since time was required for the electrode to absorb water and no pulling tension was applied during pressing, wrinkles occurred in the electrode tab area, and a good product could not be obtained.

[0159] Therefore, according to the method of the embodiment, it is possible to improve tact time (production efficiency) and yield.

[0160] According to at least one of these embodiments or examples of the electrode manufacturing method, the process includes the steps of applying a slurry containing at least one of a niobium-containing oxide and a titanium-containing oxide and water to a current collector to obtain a structure, drying the slurry to form an active material-containing layer, pressing the structure, and stacking a plurality of structures and drying the outermost layers of both of the resulting stacks under pressure to reduce the moisture content of the active material-containing layer to 600 mass ppm or less as measured by the Karl Fischer method. This reduces the occurrence of defects during transportation and insulation defects in the electrode group, thereby improving the manufacturing yield.

[0161] Although several embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims.

[0162] The invention according to the embodiments will be described below. <1> A step of obtaining a structure by applying a slurry containing water and at least one of a niobium-containing oxide and a titanium-containing oxide to a current collector; drying the slurry to form an active material-containing layer; pressing the structure; a step of laminating a plurality of the structures and drying both outermost layers of the obtained laminate under pressure, thereby reducing the moisture content of the active material-containing layer to 600 ppm by mass or less as measured by the Karl Fischer method; A method for producing an electrode comprising the steps of: <2> The drying of the slurry is carried out so that the water content of the active material-containing layer, as measured by the Karl Fischer method, is 1,000 ppm by mass or more and 10,000 ppm by mass or less. <1> A method for producing the electrode according to claim 1. <3> the coating is performed while the current collector is being moved in a transport direction, except for at least an end portion of the current collector parallel to the transport direction; The slurry is dried while the structure is moved in the transport direction and while the end portion of the structure is pulled in a direction intersecting the transport direction. <1> or <2> A method for producing the electrode according to claim 1. <4> The method further includes a step of adjusting a tension applied to the structure in a transport direction according to the moisture content. <1> ~ <3> 13. A method for producing the electrode according to any one of claims 1 to 12. <5> After the pressing, the pressing step further comprises cutting the structure. <1> ~ <4> 13. A method for producing the electrode according to any one of claims 1 to 12. <6> The niobium-containing oxide has the general formula Li x Ti 1-y M1 y Nb 2-z M2 z O 7+δ Niobium-containing oxides represented by the general formula Li x Ti 1-y M3 y+z Nb 2-z O 7-δThe niobium-containing oxide includes at least one selected from the group consisting of niobium-containing oxides represented by the formula: The M1 is at least one selected from the group consisting of Zr, Si, and Sn, the M2 is at least one selected from the group consisting of V, Ta, and Bi, the M3 is at least one selected from the group consisting of Mg, Fe, Ni, Co, W, Ta, and Mo, the x satisfies 0≦x≦5, the y satisfies 0≦y<1, the z satisfies 0≦z<2, and the δ satisfies -0.3≦δ≦0.3, <1> ~ <5> 13. A method for producing the electrode according to any one of claims 1 to 12. <7> The titanium-containing oxide includes at least one selected from the group consisting of monoclinic titanium dioxide, anatase titanium dioxide, rutile titanium dioxide, and bronze titanium dioxide. <1> ~ <6> 13. A method for producing the electrode according to any one of claims 1 to 12. <8> <1> ~ <7> a step of preparing an electrode group by using the electrode obtained by the method according to any one of the steps 1 to 5 as a first electrode and disposing a separator between the first electrode and a second electrode; A step of housing the electrode group in an exterior member; and causing the electrode group housed in the exterior member to retain a non-aqueous electrolyte. [Explanation of symbols]

[0163] Reference Signs List 1...electrode group, 2...exterior member, 3...negative electrode, 3a...negative electrode current collector, 3b...negative electrode active material-containing layer, 3c...negative electrode current collector tab, 4...separator, 5...positive electrode, 5a...positive electrode current collector, 5b...positive electrode active material-containing layer, 5c...positive electrode current collector tab, 6...negative electrode terminal, 7...positive electrode terminal, 10...structure, 20...slurry coating device, 21...drying furnace, 22...curve correction section, 23...slurry storage section, 24...first die coater, 25...second die coater, 26...current collector roll, 27...winding roller, F1...conveyor Feed path, 28...guide roller, 29...conveyor roller, 31...structural roll, 32...manufacturing apparatus, 33, 34...press rollers, 35-39...guide rollers, 40...winding section, 50...casing, 51...container, 52...cover plate, 53...bottom plate, 54...spring member, 100...secondary battery, S1...slurry coating, S2...first drying, S3...pressing, S4...cutting, S5...second drying, S6...electrode group production, S7...storing electrode group in exterior member, S8...storing electrolyte in exterior member, S9...sealing.

Claims

1. A step of obtaining a structure by applying a slurry containing water and at least one of a niobium-containing oxide and a titanium-containing oxide to a current collector; drying the slurry to form an active material-containing layer; pressing the structure; a step of laminating a plurality of the structures and drying both outermost layers of the obtained laminate under pressure, thereby reducing the moisture content of the active material-containing layer to 600 ppm by mass or less as measured by the Karl Fischer method; A method for producing an electrode comprising the steps of:

2. The method for producing an electrode according to claim 1 , wherein the slurry is dried so that the water content of the active material-containing layer, as measured by the Karl Fischer method, is 1,000 ppm by mass or more and 10,000 ppm by mass or less.

3. the coating is performed while the current collector is being moved in a transport direction, except for at least an end portion of the current collector parallel to the transport direction; The method for manufacturing an electrode according to claim 2 , wherein the slurry is dried while the structure is moved in the transport direction and while the end portion of the structure is pulled in a direction intersecting the transport direction.

4. The method for manufacturing an electrode according to claim 3 , further comprising the step of adjusting a tension applied to the structure in a transport direction according to the moisture content.

5. The method for manufacturing an electrode according to claim 1 , further comprising the step of cutting the pressed structure after the pressing.

6. The niobium-containing oxide has the general formula Li x Ti 1-y M1 y Nb 2-z M2 z O 7+δ Niobium-containing oxides represented by the general formula Li x Ti 1-y M3 y+z Nb 2-z O 7-δ The niobium-containing oxide includes at least one selected from the group consisting of niobium-containing oxides represented by the formula:

2. The method for producing an electrode according to claim 1, wherein M1 is at least one selected from the group consisting of Zr, Si, and Sn, M2 is at least one selected from the group consisting of V, Ta, and Bi, M3 is at least one selected from the group consisting of Mg, Fe, Ni, Co, W, Ta, and Mo, x satisfies 0≦x≦5, y satisfies 0≦y<1, z satisfies 0≦z<2, and δ satisfies −0.3≦δ≦0.

3.

7. 2. The method for producing an electrode according to claim 1, wherein the titanium-containing oxide comprises at least one selected from the group consisting of monoclinic titanium dioxide, anatase titanium dioxide, rutile titanium dioxide, and bronze titanium dioxide.

8. a step of preparing an electrode group by using the electrode obtained by the method according to any one of claims 1 to 7 as a first electrode and disposing a separator between the first electrode and a second electrode; A step of housing the electrode group in an exterior member; and causing the electrode group housed in the exterior member to retain a non-aqueous electrolyte.

Citation Information

Patent Citations

  • Secondary battery, battery pack and vehicle

    JP2018156895A

  • Secondary battery, battery pack and vehicle

    JP2019053944A

  • Secondary battery, battery pack and vehicle

    JP2021150194A

  • Active material, electrode, secondary battery, battery pack, and vehicle

    JP2022133777A

  • Nonaqueous electrolyte secondary battery

    WO2018123526A1

Cited By

  • Method for manufacturing electrode and method for manufacturing battery

    JP2025018737A

  • Method for manufacturing electrodes and method for manufacturing batteries

    JP7895913B2